Dirofilaria spp. And angiostrongylus vasorum: Current risk of spreading in central and northern europe - Fuehrer H. -P.; Morelli S.; Unterkofler M. S.; Bajer A.; Bakran-Lebl K.; Dwuznik-Szarek D.; Farkas R.; Grandi G.; Heddergott M.; Jokelainen P.; Knific T.; Leschnik M.; et al. (Pathogens, 2021)
In the past few decades, the relevance of Dirofilaria immitis and Dirofilaria repens, causing cardiopulmonary and subcutaneous dirofilariosis in dogs and cats, and of Angiostrongylus vasorum, causing canine angiostrongylosis, has steadily increased in Central and Northern Europe. In this review, a summary of published articles and additional reports dealing with imported or autoch-thonous cases of these parasites is provided for Central (Austria, Czechia, Germany, Hungary, Lux-emburg, Poland, Slovakia, Slovenia, and Switzerland) and Northern (Denmark, Finland, Iceland, Norway, and Sweden) Europe. Research efforts focusing on Dirofilaria spp. and A. vasorum have varied by country, and cross-border studies are few. The housing conditions of dogs, pet move-ments, the spread of competent vectors, and climate change are important factors in the spread of these nematodes. Dogs kept outside overnight are a major factor for the establishment of Dirofilaria spp. However, the establishment of invasive, diurnal, synanthropic, competent mosquito vectors such as Aedes albopictus may also influence the establishment of Dirofilaria spp. The drivers of the spread of A. vasorum remain not fully understood, but it seems to be influenced by habitats shared with wild canids, dog relocation, and possibly climatic changes; its pattern of spreading appears to be similar in different countries. Both Dirofilaria spp. and A. vasorum merit further monitoring and research focus in Europe.